Relationship between physical activity and long-term outcomes in patients with stable coronary artery disease. (March 2020) - Biscaglia, Simone; Campo, Gianluca; Sorbets, Emmanuel; Ford, Ian; Fox, Kim M; Greenlaw, Nicola; Parkhomenko, Alexander; Tardif, Jean-Claude; Tavazzi, Luigi; Tendera, Michal; Wetherall, Kirsty; Ferrari, Roberto; et al.
Aims: The aims of this study were to ascertain the relationship between level of physical activity and outcomes and to discriminate the determinants of physical activity performance or avoidance. Methods: CLARIFY is an international prospective registry of 32, 370 consecutive outpatients with stable coronary artery disease who were followed for up to five years. Patients were grouped according to the level and frequency of physical activity: i) sedentary ( n = 5223; 16.1%); ii) only light physical activity most weeks (light; n = 16, 634; 51.4%); iii) vigorous physical activity once or twice per week (vigorous ≤ 2×; n = 5427; 16.8%); iv) vigorous physical activity three or more times per week (vigorous >2×; n = 5086; 15.7%). The primary outcome was the composite of cardiovascular death, myocardial infarction and stroke. Results: Patients performing vigorous physical activity ≤2 × had the lowest risk of the primary outcome (hazard ratio, 0.82; 95% confidence interval, 0.71–0.93; p = 0.0031) taking the light group as reference. Engaging in more frequent exercise did not result in further outcome benefit. All-cause death, cardiovascular death, and stroke occurred less frequently in patients performing vigorous physical activity ≤2×. However, the rate of myocardial infarction was comparable between the four physical activity groups. Female sex, peripheral artery disease, diabetes, previous myocardial infarction or stroke, pulmonary disease and body mass index all emerged as independent predictors of lower physical activity. Conclusion: Vigorous physical activity once or twice per week was associated with superior cardiac outcomes compared with patients performing no or a low level of physical activity in outpatients with stable coronary artery disease.